Papio cynocephalus Endogenous Retrovirus among Old World Monkeys: Evidence for Coevolution and Ancient Cross-Species Transmissions - Mang, Rui (American Society for Microbiology, 2000)
To study the evolutionary history of Papio cynocephalus endogenous retrovirus (PcEV), we analyzed the distribution and genetic characteristics of PcEV among 17 different species of primates. The viral pol-env and long terminal repeat and untranslated region (LTR-UTR) sequences could be recovered from all Old World species of the papionin tribe, which includes baboons, macaques, geladas, and mangabeys, but not from the New World monkeys and hominoids we tested. The Old World genera Cercopithecus and Miopithecus hosted either a PcEV variant with an incomplete genome or a virus with substantial mismatches in the LTR-UTR. A complete PcEV was found in the genome of Colobus guereza—but not in Colobus badius—with a copy number of 44 to 61 per diploid genome, comparable to that seen in papionins, and with a sequence most closely related to a virus of the papionin tribe. Analysis of evolutionary distances among PcEV sequences for synonymous and nonsynonymous sites indicated that purifying selection was operational during PcEV evolution. Phylogenetic analysis suggested that possibly two subtypes of PcEV entered the germ line of a common ancestor of the papionins and subsequently coevolved with their hosts. One strain of PcEV was apparently transmitted from a papionin ancestor to an ancestor of the central African lowland C. guereza.